BREADFRUIT PEEL AS THE MOST POTENT RADICAL SCAVENGERS FOR SKIN PROTECTION - Syamsurizal Syamsurizal; Elisma Elisma; Puspa Dwi Pratiwi (LPPM Universitas Jambi, 2024)
The sun's ultraviolet radiation causes erythema, premature aging, sunburn, hyperpigmentation, inflammation, and dry skin. For this purpose, sunscreen with an SPF value of over 15 is needed to protect the skin against UV rays. Breadfruit peel containing flavonoids may protect against free radicals and UV radiation. This study aims to increase SPF value from breadfruit fractionate by combining niacinamide and alpha-tocopherol. The ABTS and BSLT methods were used to screen potent free radical scavengers in n-hexane, dichloromethane, ethyl acetate, and methanol extracts. The dichloromethane extract had the highest potential as a free radical scavenger, with IC50 20,90 more or less 0,54, and the lowest toxicity, with LC50 234,42 more or less 1,06. Then, the scavenging activities and selective index of fractionates of dichloromethane were evaluated to show that the DM2 fraction had the strongest free radical scavenging activity and the lowest toxicity, with the highest selective index value of 46.08. The main active ingredient was DM2, combined with niacinamide and alpha-tocopherol into five compositions. The results of the lotion dosage forms revealed that the fifth formula, F5, met the requirement SNI standards and was stable during storage, with an SPF value of 20.61 more or less than 0.75, which was three times higher than the positive control with an SPF value of 6.67 more or less 1.28.